Desenvolvimento de um jogo para android utilizando recursos de acelerômetro e tela sensível ao toque - Medeiros, Leandro Rempel (2013)
Nowadays, with technological developments, tablets and smartphones, we have a power processing equivalent to many computers, and thus become one exciting platform for game development. The market for mobile games is increasing and favorable for independent developers, whether by tools free for development, whether the facilities for sale and distribution applications using online tools like Google Play. Thus, this work presents the development of a game for the Android platform controlled by one touch screen and also the accelerometer of the device. for this developing a study about the tools for development and the technologies to control the game (touchscreen and accelerometer). To facilitate the development, a framework was proposed and encoded. The result was a didactic game, where the complexity of the code was decreased considerably by the use of the framework. At the end of the development, application was made available on the platform Google Play.